Can the potential for tick infestation influence patterns of resource use by Eland (Taurotragus oryx)? - McCulloch, Douglas John (My University, 2016)
The vegetation of the Kgaswane Mountain Reserve, in North West Province, South Africa, was mapped according to seven vegetation structure types, based on tree density and height, and grass height. Free-living ticks were collected by drag-sampling the vegetation from each structure type in November 2014, prior to the onset of the summer rains, and February 2015, once most of the seasonal rains had fallen. Eland (Taurotragus oryx) location information was recorded from four GPS collared cows over the two sample periods. Tick abundance was consistently lower in shorter, open, more exposed vegetation structure types, and higher in more sheltered types. Position higher up in the landscape nullified the positive impacts of trees on beneath-canopy microclimate in tall open woodlands, as indicated by comparatively lower tick numbers than in more sheltered woodland types. Tick abundance is influenced by vegetation structure and the availability of hosts. The majority of ticks trapped during both periods were larvae, with nymphs mostly present in November and adults mostly present later in the season, indicating the seasonal nature of tick cohort recruitment. Eland calving behaviour centred on areas with low adult tick abundance. Eland did not respond to total tick abundance during either sampling period. They did select areas with low adult tick abundance, and avoided areas with high adult tick abundance. This corresponded with an improvement in upland forage quality, which allowed them to avoid foraging in areas with high adult tick abundance. It is plausible that the potential for infestation by adult ticks may be a supplementary influence driving the use of space by eland.
A research report submitted to the Faculty of Science, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science (Resource Conservation Biology). Johannesburg, 2015
Keywords: Ticks -- South Africa.; Elands -- South Africa.; Habitat selection.; Resource partitioning (Ecology) -- South Africa -- North West Province.